2022
DOI: 10.3390/polym14102115
|View full text |Cite
|
Sign up to set email alerts
|

Thermocatalytic Conversion of Plastics into Liquid Fuels over Clays

Abstract: Recycling polymer waste is a great challenge in the context of the growing use of plastics. Given the non-renewability of fossil fuels, the task of processing plastic waste into liquid fuels seems to be a promising one. Thermocatalytic conversion is one of the methods that allows obtaining liquid products of the required hydrocarbon range. Clays and clay minerals can be distinguished among possible environmentally friendly, cheap, and common catalysts. The moderate acidity and the presence of both Lewis and Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…When applied to the pyrolysis process, they improve the product yields, allow obtaining liquid products of the required hydrocarbon range, and reduce tar formation. The comprehensive review of the thermocatalytic conversion of plastics over clays has already been summarized by Seliverstov et al [88] and Fadillah et al [89]. In some of the works reviewed, kaolin was found to act as a catalyst during the pyrolysis of different plastic feedstocks: virgin high-density polyethylene (HDPE), HDPE waste, and mixed plastic waste (MPW) by Auxilio et al [90].…”
Section: Other Fuel-related Applications Of Aluminosilicate Clay Mine...mentioning
confidence: 99%
See 1 more Smart Citation
“…When applied to the pyrolysis process, they improve the product yields, allow obtaining liquid products of the required hydrocarbon range, and reduce tar formation. The comprehensive review of the thermocatalytic conversion of plastics over clays has already been summarized by Seliverstov et al [88] and Fadillah et al [89]. In some of the works reviewed, kaolin was found to act as a catalyst during the pyrolysis of different plastic feedstocks: virgin high-density polyethylene (HDPE), HDPE waste, and mixed plastic waste (MPW) by Auxilio et al [90].…”
Section: Other Fuel-related Applications Of Aluminosilicate Clay Mine...mentioning
confidence: 99%
“…The highest liquid yields of 100 wt.% for HDPE pyrolysis over bentonite (50 wt.%) and spent fluid catalytic cracking catalyst (FCC) were obtained by Elordi et al [92], and 99.82 wt.% for pyrolysis of low-density polyethylene (LDPE) on neat kaolin powder were obtained by Erawati et al [93]. The reviewed research reveals that Seliverstov et al [88] concluded that the modification of clay minerals (e.g., acid-washing or pillaring) was helpful to achieve a higher yield of the liquid fraction in some reviewed cases, but in others, pure clays also showed excellent catalytic activity.…”
Section: Other Fuel-related Applications Of Aluminosilicate Clay Mine...mentioning
confidence: 99%